The incidental vocabulary acquisition by ESL learners through selected English songs : a case study - Ku 'Aisyahtul Radhiah binti Ku Abdul Razak (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Incidental vocabulary acquisition in ESL had been pioneered in the area of reading. However, regardless of the positive aspects people are claiming, there are limitations in the use of incidental vocabulary acquisition through reading. Some research had shown low retention rate of word meanings and the effectiveness of this method may at times be limited to English learners of low proficiency level. Thus, a new method utilizing incidental vocabulary acquisition was embarked on and the use of songs had been introduced to overcome the limitations in the previous method. This research aims to investigate whether the use of selected English songs affect vocabulary acquisition of second language learners. This was done by i) identifying whether the ESL learners acquire incidental vocabulary acquisition by listening to English songs, ii) identifying the factors influencing the incidental acquisition of vocabulary from English songs and iii) looking at the sentences constructed from incidental vocabularies. To discover the effectiveness of this mode of vocabulary acquisition, a vocabulary scale, the Vocabulary Knowledge Scale (VKS) was used with the same vocabulary items answered by fifteen ESL learners in the Pre-test and Post-test. The ESL learners were Postgraduate students majoring in Arabic language. Paired sample t-test from SPSS was calculated and interviews were conducted. The results found that there was a significant difference between the scores from the pre-test and post-test. However, the increase in the level of vocabulary knowledge by the learners was not pervasive. They have shown low increase rate from each level of the VKS and this was mainly due to the problem of inability to grasp the word pronunciation by the singers. In addition, there were other factors such as the low rate of listening skill, unfamiliarity with English songs, lack of exposure to the English language, least number of word repetition and lack of interest and different preferences among students. This study provides an insight into the pedagogical potential of using English songs as part of learning the English language.